2009
DOI: 10.1085/jgp.200810186
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent modulation of CFTR gating by pyrophosphate

Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) is an adenosine triphosphate (ATP)-gated chloride channel. ATP-induced dimerization of CFTR's two nucleotide-binding domains (NBDs) has been shown to reflect the channel open state, whereas hydrolysis of ATP is associated with channel closure. Pyrophosphate (PPi), like nonhydrolytic ATP analogues, is known to lock open the CFTR channel for tens of seconds when applied with ATP. Here, we demonstrate that PPi by itself opens the CFTR channel in a Mg2+-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
91
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(102 citation statements)
references
References 59 publications
10
91
1
Order By: Relevance
“…Furthermore, such prolongation of the opening burst became even more prominent at higher [ATP] (Fig. 3B), an observation not only corroborating the hypothesis that Vx-770 promotes the ATP-dependent reentry mechanism, but also distinguishing itself from the well-known increase of the open time by abolishing ATP hydrolysis (12,28,(30)(31)(32) We also measured the relaxation time constant of macroscopic current after removing different concentrations of ATP. In the presence of 200 nM Vx-770, these relaxation time constants are not significantly different over a wide range of [ATP] (Fig.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Furthermore, such prolongation of the opening burst became even more prominent at higher [ATP] (Fig. 3B), an observation not only corroborating the hypothesis that Vx-770 promotes the ATP-dependent reentry mechanism, but also distinguishing itself from the well-known increase of the open time by abolishing ATP hydrolysis (12,28,(30)(31)(32) We also measured the relaxation time constant of macroscopic current after removing different concentrations of ATP. In the presence of 200 nM Vx-770, these relaxation time constants are not significantly different over a wide range of [ATP] (Fig.…”
supporting
confidence: 78%
“…A fast solution exchange perfusion system (SF-77B; Warner Instruments) was used for recordings that require ligand exchange. The dead time of solution change is ∼30 ms (30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar functional asymmetry of CFTR's two NBDs was observed when the Walker A lysine residues in NBD1 (K464) and 2 (K1250) were mutated (Powe et al 2002;Vergani et al 2003). The critical role of this p-electron stacking interaction between ATP and the binding pocket also explains why pyrophosphate (PPi), a ligand without the adenine ring for this stacking interaction, shows a very low apparent affinity as a channel opener (Tsai et al 2009). Lately, capitalizing on both structural information and bioinformatics, Szollosi et al (2010) were able to experimentally show an induced fit mechanism following ATP binding to the head subdomain of NBD2 during CFTR gating.…”
Section: Gating Of Cftr Channels By Atp Binding and Hydrolysismentioning
confidence: 73%
“…Using nonhydrolyzable ATP analogs (e.g., PPi or AMP-PNP) as ligands, Tsai et al (2009) showed that contrary to ATP-gated channels that show an open time of 400 ms (Zeltwanger et al 1999), the open time for PPi-opened channels is 30 s (inferred from deactivation rates) when this ligand is applied shortly after removal of ATP, but the open time becomes much shorter ( 1.5 s) if PPi is applied minutes after ATP washout (Tsai et al 2009). Thus, CFTR channels, once primed by ATP, respond to PPi differently depending on the washout time.…”
Section: Roles Of Nbd Dimerization In Cftr Gatingmentioning
confidence: 99%